2001
DOI: 10.1159/000050460
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Logistic Regression Analysis of Risk Factors for the Development of Steroid-Dependent Asthma in the Elderly: A Comparison with Younger Asthmatics

Abstract: Background: The percentage of the aged among all patients with bronchial asthma is increasing. Objective: To investigate the risk factors for the development of steroid-dependent asthma in the elderly. Methods: A multiple logistic regression analysis involving various clinical factors between steroid-dependent and -independent asthma was carried out for 59 asthmatics aged over 60 years, including 16 patients with steroid-dependent asthma. The calculated risk for each factor was compared with that obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The present study showed that the incidence of steroid resistance is increased among all patients' age rang. This is come in agreement with that reported by Ishioka and his co-workers (30) . However, resistance to steroid did not significantly affected by sex variation, but may be linked to other factors such as smoking habit and presence of atopic allergy, a finding supported by what reported by others (31,32) .…”
Section: Discussionsupporting
confidence: 94%
“…The present study showed that the incidence of steroid resistance is increased among all patients' age rang. This is come in agreement with that reported by Ishioka and his co-workers (30) . However, resistance to steroid did not significantly affected by sex variation, but may be linked to other factors such as smoking habit and presence of atopic allergy, a finding supported by what reported by others (31,32) .…”
Section: Discussionsupporting
confidence: 94%
“…The NP incidence in asthma patients is 4-32%, but in the presence of asthma with analgesic intolerance, the incidence increases to 48-95%. [24][25][26] In the present study, only incomplete data could be In asthma patients, the presence of NP appears to be a risk factor for increased severity of asthma. 27 The incidence of NP in severe asthma patients is high.…”
Section: Discussionmentioning
confidence: 70%
“…Of adult asthma patients, 3–21% have analgesic intolerance. The NP incidence in asthma patients is 4–32%, but in the presence of asthma with analgesic intolerance, the incidence increases to 48–95% 24–26 . In the present study, only incomplete data could be obtained from patients regarding their analgesic intolerance.…”
Section: Discussionmentioning
confidence: 83%
“…The relationship between chronic sinusitis and severe asthma has been previously studied, but the results have been conflicting. For instance, in a study by Ishioka et al, 12 no association was found between chronic sinusitis and severe, steroid-dependent asthma in adult patients. However, Bresciani et al 13 found that a greater degree of clinical rhinosinusitis severity and sinus CT abnormality in patients with severe compared to mild-to-moderate asthma.…”
Section: Discussionmentioning
confidence: 88%